LI-FI TECHNOLOGY AND THE NEW CONCEPT OF DATA TRANSFER SECURITY - Ramona DUMITRAȘCU (Challenges of the Knowledge Society)
Li-Fi is a wireless technology that transmits high-speed data using visible light communication (VLC), it can achieve speeds of 224 gigabits per second in the lab. The potential Li-Fi technology can change a lot in virtual word considering it can provide transmission at 1 GB per second - that's 100 times faster than current average Wi-Fi speeds. By flickering the light from a single LED, Li-Fi technology can transmit far more data than a cellular tower, using Visible Light Communication (VLC) technology - a medium that uses visible light between 400 and 800 terahertz (THz). It works basically like an incredibly advanced form of Morse code - flicking an LED on and off at extreme speeds and can be used to write and transmit things in binary code. The benefit of Li-Fi over Wi-Fi, other than potentially much faster speeds, is that because light cannot pass through walls, it makes it a whole lot more secure.